THE VALUES OF PK1 + PK2 FOR THE DISSOCIATION OF CARBONIC ACID IN SEAWATER - Mojica Prieto F.J.; Millero F.J. (My University, 2002)
The values of pK1 + pK2 for the dissociation of carbonic acid have been determined in seawater as a function of temperature (0 to 45°C) and salinity (5 to 42). They were determined by the addition of NaHCO3 to seawater stripped of CO2 until the pH0 = 1/2(pK1 + pK2) was constant. The pH0 was measured using potentiometric and spectrophotometric techniques. The values of pH0 determined by the two methods are in good agreement (+/- 0.002). Our values of 1/2(pK1 + pK2) are in good agreement (0.005) with the results of Mehrbach et al. (1973) and the combined data have been fitted to the equation1/2(pK1+pK2)=-247.8958+6.564628 S-3.322x10-4 S2+12074.50/T+37.764148 ln T+(-290.721 S+0.12980 S2)/T-0.983517 S ln Twith a σ = 0.0052. Both studies indicate that the measurements of pK2 in artificial seawater are lower than the values in real seawater. Values of the pK1 in seawater were also determined from potentiometric titrations of seawater at a few temperatures (15 to 45°C). The results are in better agreement (0.01) with the results of Mehrbach et al. between 20 to 30°C than other workers. Our results and those of Mehrbach et al. have been combined to yield (σ = 0.0056)pK1=-43.6977-0.0129037 S+1.364x10-4 S2+2885.378/T+7.045159 ln Tand (σ = 0.010)pK2=-452.0940+13.142162 S-8.101x10-4 S2+21263.61/T+68.483143 ln T+(-581.4428 S+0.259601 S2)/T-1.967035 S ln TThese studies indicate that the values of K1 (SW) > K1 (ASW) by ~0.01 and K2 (SW) < K2 (ASW) by ~0.04 near 25°C. Measurements of pK1 + pK2 and pK1 in artificial seawater with and without boric acid show the same trends, indicating that the effect is due to interactions of boric acid with HCO3- and CO32-. Further studies are needed to elucidate these interactions.